Campaign-Style Paired Assistance: The Chinese Experience in Fighting the COVID-19 Pandemic. Issue 1 (June 2021) - Wu, Weixu; Tan, Xinyu; Jiang, Qinzhi
To cope with the COVID-19 pandemic, the Chinese government initiated a medical resource allocation and assistance mechanism that was characterized as a large-scale and regional mutual approach. Specifically, thirty provinces delivered medical resources (e.g., medical staff, medical supplies, and living materials) to "1+16" cities severely affected by the epidemic within a small amount of time, which solved the dilemma of medical collapse and governance "downtime" in epidemic areas, thereby changing the prevalence curve of the pandemic in China. "Campaign-style" targeted assistance can be interpreted based on the Chinese dual party-government model as well as the governance model of vertical accountability and horizontal competition, drawing from previous experience of normalized "designated assistance." Consequently, paired assistance contributes to intergovernmental situations of decreasing divisibility and increasing cooperation. This study has the potential to bring insights to other countries around the world that are fighting the COVID-19 pandemic.